2021
DOI: 10.1051/e3sconf/202125811011
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the development of renewable energy and state policy in improving energy efficiency

Abstract: This article examines the state policy in the field of electric power industry aimed at increasing energy saving. Taking into account all the pros and cons of classical types of electricity production, more and more attention is paid to new, emerging sources, in particular, biofuels and processing of production and consumption waste. Wind power is an innovation that has received investment for development before, but the previous advanced production has not had much success. Russia and the international commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…An integrated assessment involves grouping indicators of a region's financial security into those that positively affect its level (stimulants) and those that negatively affect its level (disincentives). In other words, the assessment is based on a comparison of actual indicators with threshold ones, and after that an integral indicator of the region's financial security is determined [10][11][12][13][14][15].…”
Section: Resultsmentioning
confidence: 99%
“…An integrated assessment involves grouping indicators of a region's financial security into those that positively affect its level (stimulants) and those that negatively affect its level (disincentives). In other words, the assessment is based on a comparison of actual indicators with threshold ones, and after that an integral indicator of the region's financial security is determined [10][11][12][13][14][15].…”
Section: Resultsmentioning
confidence: 99%
“…The first applies to the selection and calculation of heat exchangers and the second to cycle calculation and compressor selection. This helps to determine the optimum value for the daily loading of vegetables, to prevent a drastic load increase on the refrigeration units and to monitor temperature fluctuations in the storage room [21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…The study also identified the need for effective governance that supports continued investment in renewable energy and energy storage, intergovernmental cooperation, and technical upgrades to the grid. Ideally, implementation of these policy and regulatory options should result in a reliable and resilient energy system, reduced emissions, and the deployment of cost-effective systems of energy storage (Niyazbekova et al 2021). Australia will need comprehensive financial incentives for renewable energy and storage.…”
Section: Discussionmentioning
confidence: 99%